Investigation of the fabomotizol dihydrochloride effect on the morphological picture of the heart left ventricle in rats with the subacute myocardial infarction - I. A. Miroshkina; A. V. Sorokina; I. B. Tsorin; V. N. Stolyaruk; M. B. Vititnova; S. A. Kryzhanovskiy; A. D. Durnev (LLC "Publisher OKI", 2022)
The purpose of the study. Investigation of the effect of the fabomotizol dihydrochloride systematic therapy on the morphological picture of the heart left ventricle (LV) in rats in the subacute period of myocardial infarction. Materials and methods. Myocardial infarction (MI) modeling was carried out using the A.Selye method. Fabomotizol dihydrochloride was administered to rats intraperitoneally 1 time per day from the 15th to the 28th day after MI at a dose of 15 mg/kg. At the end of the experiment, euthanasia and a pathoanatomic autopsy were performed. Samples of hearts after fixation in formalin and standard wiring were poured into paraffin blocks. Histological sections of the hearts were microscoped in transmitted light. Results. Dilation of the LV cavity and thinning of its walls in animals treated with fabomotizol dihydrochloride are less pronounced than in control rats with MI. In the periinfarction zone of the myocardium in rats treated with fabomotizol dihydrochloride, wave-like deformation and fragmentation of cardiomyocytes is less intense, and the transverse striation of myofibrils, on the contrary, is more pronounced than in the control. In animals treated with fabomotizol dihydrochloride, the periinfarction zone is well vascularized. Conclusion. According to the results of morphological studies performed on a model of subacute MI in rats, it was demonstrated that systematic therapy with fabomotizole dihydrochloride contributes not only to a significant reduction in the necrosis zone, but also to a certain extent prevents the development of early postinfarction remodeling. In rats treated with fabomotizol dihydrochloride, in contrast to control animals, reparative processes prevail in the cardiac muscle. These observations indicate the presence of cardioprotective activity in the drug.